Esophageal cancer developed in a radiated field: can we reduce the risk of a poor prognosis cancer? - Schena, Marina; Battaglia, Angelo F.; Munoz, Fernando (Journal of Thoracic Disease, 2017)
Treatment options for patients with clinically localized cancer diagnosis include radiation therapy and chemotherapy. Each option is associated with side effects. Progress in cancer therapy has increased multimodality approach such as chemoradiotherapy, and patient’s life expectancy as well.